Pengaruh Tingkat Kesehatan Bank dan Corporate Social Responsibility pada Nilai Perusahaan Perbankan - Anggarsini, Ni Wayan; Suprasto, Herkulanus Bambang (E-Jurnal Akuntansi; Vol 25 No 2 (2018)DO - 10.24843/EJA.2018.v25.i02.p19, 2018)
The strategic functi on of the banking sector in the country's economic development requires banks to always maintain their firm value. This study aims to obtain empirical evidence of the effect of bank health level proxied by credit risk, good corporate governance, earnings and capital and corporate social responsibility on firm value of bank.   The population used is all banking companies listed on the Stock Exchange in 2012-2015 as many as 41 companies. The sample of the research is 22 companies by using nonprobability sampling method, that is purposive sampling technique . Data analysis technique used in this research is multiple linear regression analysis. The results of this study is show that good corporate governance, earnings and capital have a positive effect on firm value of bank. Credit risk is not proven to have a negative effect on firm value of bank and corporate social responsibility is not proven to have a positive effect on firm value of bank. Keywords : bank health level, corporate social responsibility, firm value, banking